Design and development of a human exoskeleton for rehabilitation - Tan, Wee Keat. (2011)
This report documents the design and development of a human exoskeleton meant to be used for assistive walking during rehabilitation, in particular for stroke patients who are suffering from partial paralysis of the lower limbs. An existing prototype (Exoskeleton Version I) was studied and evaluated to identify design flaws and investigate their root causes. Modifications were made to the corresponding components with problems and a second prototype known as Exoskeleton Version II was created. Existing work in the area of biomechanics were carefully reviewed to gain design insights. Human gait was also keenly studied to fully understand the motion of the human lower limbs during walking. Knowledge gained from these areas of research was incorporated in the design and assembly of the Exoskeleton Version II, in particular the two major aspects of this design project. They are namely, the selection of actuation system and gait planning for the Exoskeleton Version II. Exoskeleton Version II was evaluated and proven successful in primary trials with a healthy human volunteer as test subject. Many gait cycles were completed with no reliability issues. Actual clinical trial with an elderly stroke patient as test subject ended with less favourable results. Poor compliance of the thigh and shank braces on the Exoskeleton Version II, coupled with the test subject’s lack of muscle strength in his lower limbs, caused difficulties in assessing the usability of the prototype initially. A harness was eventually utilised to provide bodyweight support and the prototype was successfully evaluated. Exoskeleton Version II is a working design that is able to provide complete gait motion for the user. The use of this prototype should be complemented with either crutches or walkers as advised by medical professionals consulted during the design phase. This ensures that patients are not totally reliant on the exoskeleton and do not lose important muscle mass gained during conventional rehabilitation sessions with physiotherapists. Gait planning was conducted to determine the correct motions that the Exoskeleton Version II will provide for the user. Control procedures were used to automate the gait motion algorithms. Recommendations on the future areas of work for Exoskeleton Version II are provided at the conclusion of this report.